State estimation of distribution networks through the real-time measurements of the smart meters - Leite, Jonatas Boas [UNESP]; Mantovani, Jose Roberto Sanches [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Smart Grids support the active participation of end customers in the energy market. The smart meters that are the most important devices of the advanced metering infrastructure (AMI) monitor the loads and energy resources. Therefore, the smart meters measure the states of a distribution network. Thereby, this work proposes the development of an algorithm that builds a scheme to estimate the states of all elements of a distribution network through the real-time measurement data. The performance of this scheme is faster than the traditional methods because this scheme of state estimation is not interactive. Moreover, the proposed algorithm is capable of building this scheme even after it has lost the communication with some smart meters once the measurement data are redundant. Lastly, the efficiency of the proposed methodology is result of a model of the distribution transformer that connects the medium-voltage (MV) and low-voltage (LV) networks. © 2013 IEEE.
Keywords: Real-Time State Estimation; Smart Grids; Smart Meter; Transformer model